The state-dependent impact of changes in bank capital requirements - Lang, Jan Hannes; Menno, Dominik (Journal of Banking & Finance, 2025)
Based on a non-linear structural banking sector model, we show that the impact of changes in bank capital requirements on lending is strongly state-dependent. When banks make profits or maintain voluntary capital buffers, the impact on lending works through a “pricing channel” which is small: 0.1% less loans for a 1pp capital requirement increase. When banks are capital-constrained, the impact on lending works through a “quantity channel” which is large: 10% more loans for a 1pp capital requirement reduction. Our results provide a theoretical justification for building up a positive neutral countercyclical capital buffer in “normal” macro-financial environments.